Anatomía foliar comparada y relaciones filogenéticas de 11 especies de Laeliinae con énfasis en Brassavola (Orchidaceae) - Noguera-Savelli, Eliana (Universidad de Costa Rica, 2011)
Brassavola inhabits a wide altitude range and habitat types from Northern Mexico to Northern Argentina. Classification schemes in plants have normally used vegetative and floral characters, but when species are very similar, as in this genus, conflicts arise in species delimitation, and alternative methods should be applied. In this study we explored the taxonomic and phylogenetic value of the anatomical structure of leaves in Brassavola; as ingroup, seven species of Brassavola were considered, and as an outgroup Guarianthe skinneri, Laelia anceps, Rhyncholaelia digbyana and Rhyncholaelia glauca were evaluated. Leaf anatomical characters were studied in freehand cross sections of the middle portion with a light microscope. Ten vegetative anatomical characters were selected and coded for the phylogenetic analysis. Phylogenetic reconstruction was carried out under maximum parsimony using the program NONA through WinClada. Overall, Brassavola species reveal a wide variety of anatomical characters, many of them associated with xeromorphic plants: thick cuticle, hypodermis and cells of the mesophyll with spiral thickenings in the secondary wall. Moreover, mesophyll is either homogeneous or heterogeneous, often with extravascular bundles of fibers near the epidermis at both terete and flat leaves. All vascular bundles are collateral, arranged in more than one row in the mesophyll. The phylogenetic analysis did not resolve internal relationships of the genus; we obtained a polytomy, indicating that the anatomical characters by themselves have little phylogenetic value in Brassavola. We concluded that few anatomical characters are phylogenetically important; however, they would provide more support to elucidate the phylogenetic relantionships in the Orchidaceae and other plant groups if they are used in conjunction with morphological and/or molecular characters.